Features of language for scientific and technical purposes - Mićić Sofija (Serbian Medical Society - Dental Section, Belgrade, 2003)
In the paper, the difference between 'general' or 'standard' and 'language for special/specific purposes' (LSP) has been pointed out. Due to the predominance of English as a leading global language, the classification of English is presented. Some terms related to LSP have been defined (register functional style, genre). Special attention was paid to genre analysis. A detailed analysis was done about scientific style with its features including the language of medicine. Finally, the importance of standardization of medical terminology in Serbian was shown by giving examples from medical journals. Some future trends in development of language for medical purposes have been outlined.